1996
DOI: 10.1021/bk-1996-0648.ch021
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Limiting Steps in Film Formation of Acrylic Latices as Elucidated with Ellipsometry and Environmental Scanning Electron Microscopy

Abstract: Our data indicate that evaporation is the rate-limiting step in film formation when the temperature of a latex is about 20 Κ or more above its glass transition temperature (T g ). When a latex is nearer to its T g , the rate-limiting step in film formation is deformation of the latex particles, possibly by viscous flow of the polymer driven by the reduction in surface energy. In this latter case, there is evidence that a drying front first creates air voids. Subsequently, a coalescence front moves inward from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…Further film formation may then proceed through a dry sintering mechanism driven by the polymer surface tension [11,12] or not at all if particles are too rigid. If the particles do not deform fast enough they will dewet.…”
Section: Full Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…Further film formation may then proceed through a dry sintering mechanism driven by the polymer surface tension [11,12] or not at all if particles are too rigid. If the particles do not deform fast enough they will dewet.…”
Section: Full Papersmentioning
confidence: 99%
“…Light-turbidimetry [10,24], interferometry [25] and evanescent dynamic light scattering [26] have been used to determine particle spacings and mobility in drying films. ESEM [11,20] and AFM [27 -29] have been applied to characterize deformation and coalescence of particles at the surface of films. Some authors observed the rupture of hydrophilic membranes and segregation of surfactant and concluded that they play an important role in the process of film formation [3,30].…”
Section: Full Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…If the particles do not deform fast enough they will dewet. Further film formation may then proceed through a dry sintering mechanism driven by the polymer surface tension [11,12] or not at all if particles are too rigid. In the cases where particle deformation is not the rate-limiting process, particle deformation proceeds along with water evaporation and is hence driven by capillary effects and by polymer -water interfacial tension [13 -16].…”
Section: Full Papersmentioning
confidence: 99%
“…Such a skin may be a porous, dry layer [9] or wet [10]. Both lateral and vertical heterogeneous drying have been considered as the same phenomenon [11]. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%